Passion fruit production under different swine wastewater doses treated in a biodigester - Vásquez, Manuel Antônio Navarro; Santos, Ana Maria Sousa; de Oliveira, Danilo Francisco; Vásquez, Edilza Maria Felipe; dos Santos, Francisco Gauberto Barros; Sousa, Francisco Rondynelle Rodrigues (Seven Editora, 2023)
Soil fertilization using materials of animal origin, such as biofertilizers, is an important practice to maintain productive soil, as they provide beneficial effects on soil's physical, chemical, and biological properties. This study aimed to evaluate the number of fruits, fruit mass, and yield of yellow passion fruits in the first year of cultivation with the application of swine wastewater (SW) treated in a biodigester. The experiment was set up at the experimental area belonging to IFCE Crato, CE, Brazil, with a spacing of 5.0 m between plants and 3.0 m between rows, using the espalier system of training and drip irrigation. The experiment was conducted in a randomized block design, with five treatments and four replications. Treatments consisted of five SW doses (D1 = 0, D2 = 0.50, D3 = 1.00, D4 = 1.50, and D5 = 2.00 L plant−1) applied at two phenological stages of the crop. The results were subjected to analysis of variance at a 5% significance, followed by the regression test. The increased SW doses influenced all the studied variables, following the linear and quadratic regression models, except for the mean fresh fruit mass. The highest yield was achieved with the highest studied dose, being an interesting alternative for recommendation to farmers in the region.DOI:https://doi.org/10.56238/alookdevelopv1-085